Análise da mobilidade urbana a pé à luz da sintaxe espacial - Rocha, Jaqueline dos Santos (2023)
Government institutions and urban planners have sought to increase pedestrian activity on city streets as part of strategies aimed at sustainability, economic development, and community growth. While urban walking mobility has recently received widespread attention in the planning literature, organizations mostly have traffic impact assessments that focus on commuting via motorized and individual transport and lack pedestrian movement impact assessments. This is because most planners do not adopt practical methods of preliminary analysis of how the proposals developed may affect pedestrian activity on streets in different urban configurations. In this way, this research seeks to collaborate with the use of computational mechanisms for city planning, approaching the Spatial Syntax Theory (SST) and its application in urban mobility on foot. For this, it elected the Neighborhood Jardim Camburi (VitóriaES) and its surrounding areas for the performance of the analyses, with the objective of developing a methodological model of diagnosis that can be replicated to the other regions of the municipality. The exploratory work used an abductive, empirical, bibliographic, and documentary method. As for the process, he made use of geographic information systems (GIS) based on the Concepts Of SST. The results were processed through the Space Syntax Toolkit (SST) plugin in the QGIS software for qualitative analysis of the measurements. They demonstrated that the part of the neighborhood that presents its orthogonal form has higher levels of Integration (INT) on a global scale. When evaluated within a radius of 500m, in addition to the orthogonal fraction, excerpts in organic formats also became integration nuclei. In the potential of Choice (CH), the roads that coincide with highways and high flow roads stood out. In this sense, the theory and methodology proved to be appropriate for the qualitative analysis of walking mobility for urban planning because from the identification of INT and CH levels, it is possible to identify microregions for specific urban planning and later correlate this information, to optimize processes and create conditions to encourage the well-being for society.